A Metataxonomic Analysis of Maple Sap Microbial Communities Reveals New Insights Into Maple Syrup Complexity - N’guyen, Guillaume Quang; Roblet, Cyril; Lagacé, Luc; Filteau, Marie (Frontiers in Systems Biology, 2022)
Maple syrup, an emblematic food product of Canada is produced from the concentration of sap collected from maple trees during spring. During this season, the trees come out of dormancy, which modifies sap composition. Meanwhile, microorganisms that contaminate sap as it is collected can also modify its composition. As these two factors can impact the quality of maple syrup, we aimed to better understand how microbial communities vary along dormancy release. We estimated the absolute abundance of bacteria and fungi in maple sap along a dormancy release index using high-throughput amplicon sequencing and digital droplet PCR (ddPCR). Several members were identified as indicators of maple sap composition, syrup organoleptic conformity and color, some of which are also hubs in the microbial association networks. We further explored bacterial communities by performing a predictive functional analysis, revealing various metabolic pathways correlated to dormancy release. Finally, we performed an experimental investigation of maple sap carrying capacity and limiting nutrients along dormancy release and found that maple sap composition variation influences its carrying capacity. Taken together, our results indicate that an increase in nitrogen supply in the form of allantoate combined with possible metabolite excretion could lead microbial communities towards different paths. Indeed, we observed a greater heterogeneity during late dormancy release which in turn could explain the variation in maple syrup quality. Further experimental investigation into the contribution of microbial, vegetal, environmental, technological, and processing factors to the final composition of maple syrup will be required to improve our understanding of this complex and flavorful food matrix and to develop quality control strategies.